Petrobras’ challenges in the development of the PreSalt reserves: is it the time for Brazil to adopt the International Energy Charter? - Guilherme Baptista Schwartsmann (Revista de Direito Econômico e Socioambiental)
According to the International Energy Agency, Brazil plays a central role in meeting the world’s oil needs through to 2035, accounting for one-third of the net growth in global supply. At the centre of the country’s efforts to become one of the world’s largest oil producers is a highly complex and capital-intensive deep-water project to develop its pre-salt basin oil reserves3. The purpose of this paper is to briefly present the pre-salt project and its production challenges – both economical and political – demonstrating the potential benefits of the adoption of the International Energy Charter for its development.